Communalism Factor in Evolution of Political Situation in British India (1920s-1930s) - A. V. Sagimbaev (Научный диалог, 2024)
This article delves into specific aspects of complex political processes that unfolded in the interwar decades in British India, serving as the foundation for the subsequent decolonization of Hindustan. Drawing from an analysis of documentary sources and literary works, a comprehensive overview is provided regarding the factors shaping Indian communalism and the conceptual perspectives of its proponents during the period under review. The study concludes on the contradictory nature of colonial policy during this period. On one hand, it contributed to the formation of elements of political culture within Indian society and to some extent laid the groundwork for India’s future federative system. On the other hand, its aim was to deepen divisions among various ethno-confessional and social groups of the Indian population to solidify control over a key segment of the British colonial system. The actions of colonial authorities significantly exacerbated relations between key ethno-confessional groups of the Indian population by the late 1930s, setting the stage for the dramatic post-World War II processes leading to the partition of British India into two sovereign entities. The complex relations between these entities largely shape the contemporary character of international relations in South Asia.